Instant Rice Semolina Upma Mix: Quick, Authentic and Nutritious Breakfast - Kumari, Resham; Wismen, Bendula; Thilsted, Shakuntala (CGIAR Impact Platform on Nutrition, Health and Food Security, 2025)
Experience the authentic flavors of South India with IRRI’s low Glycemic Index (GI) instant rice semolina upma mix. This gluten-free, 5-minute breakfast delight contains no artificial flavors, colors, or preservatives, and is rich in micronutrients. Blending premium rice semolina (rava) with a curated selection of spices and seasonings, this mix offers a convenient and nutrition option for a quick and delicious breakfast, capturing the essence of traditional South Indian cuisine. This video is produced by IRRI, with funding from the CGIAR Nutrition Impact Platform's Nutrition-sensitive Food Systems Impact Video grant.